Flow Characteristics of a Rich-Quench-Lean Combustor-Combined Low-Emission and High-Temperature Rise Combustion - Jianzhong Li; Jian Chen; Li Yuan; Ge Hu; Jianhan Feng (International Journal of Aerospace Engineering)
To determine the flow field structure and flow characteristics of a rich-quench-lean (RQL) combustor-combined low-emission and high-temperature rise combustion, a two-dimensional PIV technology was used to evaluate the effect of aerodynamic and structural parameters on the flow field and flow characteristics of the combustor. The variation in the total pressure loss of the combustor has little effect on the flow field structure of the combustor. However, the variation in the parameters of primary holes significantly affects the structure of the central recirculation zone, the distribution of local recirculation zones in the rich-burn zone and quenching zone, and the average residence time in the quenching zone. On the plane that passes through the center of the primary hole, the variations in the array mode and diameter of primary holes would form entrainment vortexes with different characteristics, thus affecting the position and flow state of local recirculation in the rich-burn zone and the local structure of the central recirculation zone. As the rotational direction of local recirculation coincides with that of the main air flow in the primary zone, the local center recirculation is intensified. In contrast, it is weakened. As the primary holes are located at half height (H/2) of the combustor, the residence time of air flow at the quenching zone can be shortened by 65% through using the staggered structure of primary holes and increasing the momentum of the partial single-hole jet. The quick-mixing process in the quenching zone is not beneficial to increase the number of primary holes and decrease the momentum of the single-hole jet.